Early-onset basal cell carcinoma - Turan, Enver; Yurt, Nurdan; Yeşilova, Yavuz; Türkçü, Gül (The Turkish Journal of Pediatrics, 2013)
Basal cell carcinoma (BCC) is a common skin cancer that is responsible for approximately 75% of non-melanoma skin cancers. BCC occurs on sunexposed areas in fair-skinned individuals; frequency increases with age and peaks in the seventh decade of life. Although it usually occurs in the elderly population, it has been reported in children as well. Here, we present a case of BCC in an eight-year-old child without any predisposing characteristics.